Analysis of MeEf1A6 Gene Promoter Activity with In-vitro and In-vivo using Transient and Stable Expression Techniques in Tobacco Plant (Nicotiana tabacum) - Galih Gibral Andalusia; Sony Suhandono; Ima Mulyama Zainuddin (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
The promoter is a part of the gene that functions in carrying out the gene expression, and its work activity becomes a matter of concern to ensure that expression works effectively. MeEF1A6 (Manihot esculenta Elongation Factor 1 Alfa - 6) is a promoter derived from cassava plants (Manihot esculenta). In previous studies, the MeEF1A6 promoter was successfully isolated, introduced, and characterized into the pBI121 plasmid, replacing the CaMV35S promoter. This study aims to analyze the activity of MeEF1A6 promoters in-vivo and in-vitro by using transient and transgenic techniques in tobacco plants. The pBI121 plasmid containing the MeEF1A6 promoter was introduced into Agrobacterium tumefaciens strain AGL1 and LBA4404. The promoter's work was then analyzed by the result of introducing it into the tobacco plant using the transient and stable transformation. The whole part of explants was used for transient study and tested in a minimum of two biological replicates. Sixty sheets of explant leaves that have been cut were used for stable transformation. The promoter work analysis was carried out with the GUS gene expression that integrated with the promoter with histochemical GUS assay. The transient produced a blue color in the roots, stems, and leaves on the whole repetition. The transverse incision in the stem shows the blue color on the epidermis and procambium tissue. Stable transformation using AGL1 as vector produced 43 shoots from 40 calli. A total of 43 shoots were selected with antibiotics and produced 27 plantlets that were successfully grown. Some plantlets are then reacted with x-gluc as histochemical GUS assay substrat and produced a blue color in the explants, indicating that the MeEF1A6 promoter has been successfully introduced. The results indicate that the MeEF1A6 promoter could work on plant tissue in roots, stems, leaves, and tissues that connect meristems such as procambium in tobacco plants. This reinforces the suspicion that the MeEF1A6 promoter performs work constitutionally as a constitutive promoter.